MEET THE HERO WHO VISITS A LIBRARY CORNER TO ENHANCE SPELLING COMPETENCE - Bulelwa Makena; Viwe Lungisani Feni (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
Library learning resources have the potential to transform language competencies. This paper aims to investigate whether daily reading activities can substantially influence spelling competence. A qualitative research approach was administered. Findings revealed that (i) one-on-one tutoring improves spelling, and (ii) collaborative learning spaces have positive impact on language development. This study concludes that a shift in language teaching-learning approaches is not only necessary but also promising, with daily reading activities being a potential core practice.